Ondansetron Use During Pregnancy: Birth Defects and Obstetric Outcomes. (May 2023) - Masarwe, Sabaa; Shvartsur, Rachel; Hadar, Eran; Betesh-Abay, Batya; Peleg, Noam; Azab, Abed N.
Ondansetron is a widely administered medication for nausea and vomiting of pregnancy. Further examination of its teratogenic capacity is necessary. This study examines the association between ondansetron treatment during pregnancy and birth defects and adverse obstetric outcomes. Patient data were extracted from Clalit Health Services, Israel. A propensity-score analysis was performed matching those exposed to ondansetron with those who were not. Findings identified 774 women exposed to ondansetron, matched 1:1 with unexposed control patients. No significant differences were found between the groups for: cleft palate, cardiovascular congenital abnormalities, spina bifida occulta, preterm delivery, or small for gestational age. Ondansetron may be a useful and safe alternative as treatment for women who suffer from hyperemesis gravidarum and do not respond to other antiemetic drugs. Notwithstanding, additional prospectively designed research is needed to establish the safety of ondansetron treatment during pregnancy.